Pro salute Non Mundi: a history of the Pan American Health Organisation (PAHO WashingtonUS, 1992)
Shows how PAHO addresses, through concerted action, major health problems as exemplified by its response to the recent cholera epidemic. Traces the progress of the organization through the years and focuses on special programmes and priorities.
DC